Relation between anti-mullerian hormone and blastocyst rate in patients less than 35 years old - Bahgat, Nagwan Ahmed; Denek, Ziya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Anti-mullerian hormone is the most commonly used predictor for in vitro fertilization cycles outcome from the quantity point of view but not the quality. Methods: The study included retrospective analysis of 247 cycles out come up to blastocyst rate. Patients included in the study were divided in to three groups according to Anti-Mullerian hormone value. Results: The primary outcome included cycles outcome rates up to blastocyst rate, cycles without blastocyst, cycles with 100% blastocyst. While secondary outcome included oocyte number, number of mature oocyte, number of fertilized oocytes, number of cleaved oocytes, number of blastocyst. We found that the mean number of blastocyst is significantly affected by AMH in favor of group C, but the blastocyst rate was not significantly affected between the three groups group A (58.16%), group B (52.56%), group C (55.49%) with p value 0.621 which is not significant. The rate of cycles with 100% blastocyst rate was not significantly different between the groups, however the rate of cycles without blastocyst was higher in group B (13.58%) but it did not differ between the groups A (7.4%) and group C (7.9%). The difference was not significant between the three groups. Conclusions: AMH can be a good predictor of IVF cycles outcome based on the ovarian yield and numerical outcome but it is not a good predictor of the blastocyst rate which could indicate the quality of the outcome of the cycles in patients 35 years of age or less.